Managerial Strategies to Enhance Vocational High School Graduates’ Work Readiness: The Roles of Internships, Motivation, and Self-Efficacy - Zulkarnaen Zulkarnaen; Jun Surjanti; Meylia Elizabeth Ranu; Elginitatea Ratigo (Institute of Multidisciplinary Research and Community Service, 2026)
Work readiness of vocational high school graduates represents a primary key performance indicator in vocational education management. The persistently high youth unemployment rate among vocational high school graduates demands outcome-based educational governance. This study examines how the quality of field work practice (PKL) experience and work-entry motivation predict student work readiness, with self-efficacy as a psychological mediator, and formulates evidence-based managerial implications for school managers. A quantitative explanatory research design was applied to a sample of 346 grade XII students from 17 schools in the industrial city of Kota Dumai, Riau Province, Indonesia (N=2,555), selected via proportional random sampling. To ensure unbiased randomization, individual student respondents within each class were selected by lottery. Data were collected using a validated 54-item questionnaire and analyzed using PLS-SEM in SmartPLS 4. Normality assessment via skewness and kurtosis confirmed that the data did not deviate extremely from normality. The reflective measurement model demonstrated satisfactory convergent validity (AVE = 0.374–0.543), reliability (CR = 0.893–0.934), and discriminant validity (HTMT 0.85). Structural model evaluation showed an acceptable fit (SRMR = 0.076) and explained 34.0% of the variance in work readiness (R² = 0.340). Hypothesis testing via 5,000-subsample bootstrapping confirmed all seven hypotheses were supported: PKL quality (β=0.284, p0.001) and motivation (β=0.226, p0.001) directly predict work readiness; both also predict self-efficacy (β=0.307, p0.001 and β=0.297, p0.001). Self-efficacy is the strongest direct predictor of work readiness (β=0.332, p0.001) and significantly mediates both paths (PKL VAF=26.4%; Motivation VAF=30.4% based on Hair et al. (2019) VAF criteria. Three managerial agendas are proposed for SMK administrators: optimizing PKL quality management, developing a school motivational climate, and integrating structured self-efficacy-building programs to facilitate successful school-to-work professional transitions. Keywords: work readiness, self-efficacy, internship experience, work motivation, vocational education.